Genetic Characterization of Coenzyme A Biosynthesis Reveals Essential Distinctive Functions during Malaria Parasite Development in Blood and Mosquito - Hart, Robert J.; Abraham, Amanah; Aly, Ahmed S. I. (Frontiers in Cellular and Infection Microbiology, 2017)
Coenzyme A (CoA) is an essential universal cofactor for all prokaryotic and eukaryotic cells. In nearly all non-photosynthetic cells, CoA biosynthesis depends on the uptake and phosphorylation of vitamin B5 (pantothenic acid or pantothenate). Recently, putative pantothenate transporter (PAT) and pantothenate kinases (PanKs) were functionally characterized in P. yoelii. PAT and PanKs were shown to be dispensable for blood stage development, but they were essential for mosquito stages development. Yet, little is known about the cellular functions of the other enzymes of the CoA biosynthesis pathway in malaria parasite life cycle stages. All enzymes of this pathway were targeted for deletion or deletion /complementation analyses by knockout/ knock-in plasmid constructs to reveal their essential roles in P. yoelii life cycle stages. The intermediate enzymes PPCS (Phosphopantothenylcysteine Synthase), PPCDC (Phosphopantothenylcysteine Decarboxylase) were shown to be dispensable for asexual and sexual blood stage development, but they were essential for oocyst development and the production of sporozoite. However, the last two enzymes of this pathway, PPAT (Phosphopantetheine Adenylyltransferase) and DPCK (Dephospho-CoA Kinase), were essential for blood stage development. These results indicate alternative first substrate requirement for the malaria parasite, other than the canonical pantothenate, for the synthesis of CoA in the blood but not inside the mosquito midgut. Collectively, our data shows that CoA de novo biosynthesis is essential for both blood and mosquito stages, and thus validates the enzymes of this pathway as potential antimalarial targets.